Management of material resources with a focus on technical complaints - Roseli Broggi Gil; Lucieli Dias Pedreschi Chaves; Ana Maria Laus (Universidade Federal de Goias, 2015)
Descriptive study aimed to characterize the process of notification of the technical complaint of consumables in a public teaching hospital, a member of Sentinela Hospital Network of the National Health Surveillance Agency. The data obtained was from the printed notices that resulted in 260 notifications analyzed from 2007 to 2009. The results showed a predominance of non-conformities in the group of medical-hospital material (80.4%) and the main complaints referred to the structure of the products used (79%). Of the total amount of notifications, 7.7% were referred to the National System of Notifications in Sanitary Surveillance. The nurses were the professionals who mostly (81.2%) made the notifications. The findings of this research revealed the importance of implementing and using systems for making systematic records of material evaluations as a basis for efficient management regarding the maximization of economic resources.